PATIENT SAFETY CULTURE AND ASSOCIATED FACTORS AMONG HEALTH CARE WORKERS IN HOAN MY SAI GON HOSPITAL, VIET NAM, 2025: A CROSS-SECTIONAL MIXED METHODS STUDY (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the existing situation of patient safety culture (PSC) and analyze factors influencing PSC at Hoan My Saigon Hospital in 2025.Methods: The study used a combination of quantitative and qualitative research methods. The study period was from December 2024 to September 2025.Results: The highest positive response rate for patient safety culture was observed in Teamwork (91,0%), while Staffing and Work pace had the lowest rate (62,6%). Individual factors including years of experience, professional title, managerial role, and work position were significantly associated with positive perceptions of patient safety culture. Qualitative findings highlighted leadership commitment, reward mechanisms, and established policies as key positive influences.Conclusion: The overall positive response rate for patient safety culture at Hoan My Saigon Hospital was high (82,8%) in 2025. Improvement efforts should prioritize domains with lower positive response rates.
Keywords: Patient safety culture, patient safety, hospital management